Six mois sur Duolingo pour apprendre le français, le chinois, et d’autres langues : An Experiential Diary Account of Linguistic Diversity - Rob Werner (Studies in Self-Access Learning Journal)
This essay is a diary account of learning French, as well as exploring eight other languages in six-months through the app, Duolingo, and how exposure to this diversity of languages has enriched my possession of cultural capital. My perspective is that of a sociology lecturer from Malaysia, specialising in ethnic studies, who also teaches Malaysian, international, and French exchange students among others, and is thus exposed to a cornucopia of languages. During the global pandemic, global trends such as the shift towards online learning and ‘levelling up’ through enhancing one’s skills, brought me to the idea of learning ‘foreign’ languages in an informal but guided sense, replete with a structured syllabus. I now recount, post-six months, my journey in learning French, my completion of two other language ‘courses’, as well as my exploration of several others, all through Duolingo. I contextualise my experience within the phenomenon of super-diversity (Vertovec, 2007), and encapsulate my benefits within Bourdieu’s (1984) concept of cultural capital in the linguistic domain.